Microwave-assisted acid pretreatment of sago wastewater for fermentable sugar production - Mohamad Puad, Noor Illi; Mohd Rashidi, Ummul Madihah; Azmi, Azlin Suhaida; Abd Wahab, Mohd Firdaus (2019)
Sago wastewater is one of by-products from the sago starch industry. In most practice, sago wastewater is discharged to the nearby rivers. As it contains high amount of organic compounds, usual practice of disposing the wastewater will cause a detrimental impact to the environment. High amount of organic compounds found in the wastewater such as starch can be utilized as substrate for biofuel and biohydrogen fermentations. However, this starch needs to first undergo pretreatment process to breakdown its complex sugars to the simpler ones. Hence, this study aims to investigate the effect of microwave-assisted acid pretreatment of sago wastewater for fermentable sugar (glucose) production using sulphuric acid (H2SO4). Three parameters that influenced microwave-assisted acid pretreatment were chosen for optimization which are residence time (3-9 min), concentration of acid (0.2-0.6 M) and solid loading (5-15% w/v). Faced Centered Central Composite Design (FCCCD) in Design Expert v9.0.6.2 software was used for designing the experiments and optimization purposes. The response was the amount of glucose converted (g/L). Based on the results, the maximum fermentable sugar produced was 3.920 g/L which was obtained at 9 minutes with 15% solid loading by using 0.6 M of H2SO4. Then, the kinetic study of acid hydrolysis was performed by following the first order reaction kinetics. The rate constant of reaction obtained was 0.1684 min-1. It can be concluded that microwave-assisted acid pretreatment of sago wastewater is able to produce high amount of fermentable sugar within a short residence time.